An Analysis of Speaking Difficulties Among University EFL Students - Anggraini, Dian; Andriani, Desi; Afersa, Mona (Jurnal Ilmiah Langue and Parole, 2025)
Speaking proficiency remains one of the most challenging components of English as a Foreign Language (EFL) learning at the university level. This study investigates the linguistic, psychological, and environmental factors contributing to speaking difficulties among university EFL students. Using a mixed-methods descriptive design, data were collected through questionnaires, speaking performance assessments, interviews, and classroom observations. Quantitative findings show that linguistic limitations—particularly restricted vocabulary (M = 4.21), inaccurate pronunciation (M = 4.07), and grammatical inaccuracies (M = 3.98)—constitute the most dominant challenges. Psychological factors also play a significant role, with high speaking anxiety (M = 4.15) and fear of negative evaluation negatively correlating with performance (r = –0.63). Environmental and pedagogical conditions further intensify these difficulties, as large class sizes, limited speaking opportunities, and teacher-centered instruction reduce authentic oral interaction. Qualitative data support these findings by revealing recurrent anxiety, limited spontaneous speech, and restricted classroom engagement. The results highlight that speaking difficulties arise from the interplay of linguistic weaknesses, affective constraints, and contextual barriers. The study recommends integrated pedagogical approaches that strengthen linguistic competence, reduce anxiety, and provide more opportunities for meaningful communication to support students’ oral proficiency development.